Evaluation of factors that contribute to the expansion and control of brassica insect pests in northern Colorado - Longtine, Zachary W., author; Cranshaw, Whitney, advisor; Kondratieff, Boris, committee member; Uchanski, Mark, committee member (Colorado State University. Libraries, 2018)
Human modifications to landscapes in agricultural areas can both eliminate and create new habitat for various organisms. One of the ways that sites are modified is by creating changes in plant communities. These can occur from physical disturbances from activities such as plowing or road building. Introduction and spread of non-native plants also greatly affects the types of plant communities common both within and outside of agricultural fields. The first part of this study consisted of an arthropod fauna survey on three non-native winter annual or perennial brassicaceous weeds that are presently common in disturbed sites in and around agricultural areas of Colorado: blue mustard, Chorispora tenella (L.), flixweed, Descurainia sophia (L.), and whitetop/hoary cress, Cardaria draba (L.). This survey was performed to see what insects, harmful and beneficial, might use them as bridge habitat between the winter and the growing season. Multiple locations where these plants are grown (typically in agricultural areas and disturbed sites) were chosen and were visited once a week during spring 2016 and 2017 and sampled with a sweep net. It was found that though flixweed supported the most genera, whitetop had the highest relative diversity in terms of both number of genera and evenness of numbers found. Blue mustard lacked in insect diversity. The most common phytophagous insects included false chinch bug (Nysius spp.), pale legume bug (Lygus elisus Van Duzee), diamondback moth, Plutella xylostella (L.) and western black flea beetle, Phyllotreta pusilla Horn. The most common natural enemy species present on the plants were parasitoid wasps and lady beetles though these and other beneficial insects were found in small numbers. It was concluded that these three brassicaceous weeds can might act as important ecological bridges for phytophagous insects. In part two of this study a test was conducted on the effects of supplemental insect food and wintergreen oil, which attract certain natural enemies, to reduce damage by certain lepidopteran pests associated with brassica crops. Plantings of broccoli, cabbage, and kale were sprayed weekly with the test treatments of supplemental insect food and supplemental insect food plus wintergreen oil. Weekly surveys of the plot were made to count numbers of imported cabbageworm, Pieris rapae (L.) and cabbage looper, Trichoplusia ni (Hübner) present and to note the presence of any natural enemy species. Harvest assessments were made of leaf injury to cabbage and the number of caterpillars present/head in broccoli. There were no significant statistical differences between treatments in regards to the number of insect pests present on plants or the injury produced.
Keywords: bridge; invasive; flea beetle; Nysius; Brassica; Lygus